Behavioral Impact of Long‐Term Chronic Implantation of Neural Recording Devices in the Rhesus Macaque. Issue 4 (17th July 2018) - Kyle, Colin T.; Permenter, Michele R.; Vogt, Julie A.; Rapp, Peter R.; Barnes, Carol A.
Abstract : Background: Ensemble recording methods are pervasive in basic and clinical neuroscience research. Invasive neural implants are used in patients with drug resistant epilepsy to localize seizure origin, in neuropsychiatric or Parkinson's patients to alleviate symptoms via deep brain stimulation, and with animal models to conduct basic research. Studies addressing the brain's physiological response to chronic electrode implants demonstrate that the mechanical trauma of insertion is followed by an acute inflammatory response as well as a chronic foreign body response. Despite use of invasive recording methods with animal models and humans, little is known of their effect on behavior in healthy populations. Objective: To quantify the effect of chronic electrode implantation targeting the hippocampus on recognition memory performance. Methods: Four healthy female rhesus macaques were tested in a delayed nonmatching‐to‐sample (DNMS) recognition memory task before and after hippocampal implantation with a tetrode array device. Results: Trials to criterion and recognition memory performance were not significantly different before vs. after chronic electrode implantation. Conclusion: Our results suggest that chronic implants did not produce significant impairments on DNMS performance.